Nerolidol-loaded nanospheres prevent hepatic oxidative stress of mice infected by Trypanosoma evansi - Baldissera M.D. (2017)
© Cambridge University Press 2016.The aim of this study was to evaluate the effect of nerolidol free (N-F) and nerolidol-loaded in nanospheres (N-NS) on the hepatic antioxidant/oxidant status of mice experimentally infected by Trypanosoma evansi. In the liver it was measured: reactive oxygen species (ROS), thiobarbituric reactive acid substances (TBARS) and non-protein thiols (NPSH), catalase (CAT), superoxide dismutase (SOD) and glutathione-S-transferase (GST) and performed histopathological examination. In addition, seric levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were measured. Liver samples from mice infected by T. evansi showed increased (P < 0·05) ROS, TBARS, AST and ALT levels and SOD activity, and decreased NPSH levels and CAT activity (P < 0·05) compared with uninfected animals. N-NS treatment prevented (P < 0·05) ROS and TBARS increase, and increased NPSH levels, and ameliorate CAT and SOD activities on liver of infected mice. Moreover, N-NS treatment reduced (P < 0·05) AST and ALT levels, and prevented histopathological changes caused by the parasite. N-NS protected the liver from the oxidative stress caused by T. evansi, which might be due to its antioxidant properties. Nerolidol might be considered a promising therapeutic agent against oxidative stress, and nanotechnology is an encouraging approach to be explored.